ESG ratings and corporate success: analyzing the environmental governance impact on Chinese companies’ performance - Chen, Sidi; Fan, Min (Frontiers in Energy Research, 2024)
This study explores the impact of ESG ratings on corporate performance, focusing on achieving sustainable development and corporate sustainability through innovation within the context of high-quality global economic growth. In recent years, ESG ratings have garnered significant attention in the financial sector, influencing corporate strategy and performance management. While some argue that ESG activities might detract from profitability, others highlight that firms with strong ESG performance can access low-cost capital, thereby enhancing overall performance. Using a sample of China’s A-share listed companies from 2009 to 2021, this research examines the influence and mechanisms of ESG ratings on corporate performance. The findings indicate a significant positive relationship between ESG ratings and corporate performance, which remains robust after rigorous testing. Mediation analysis reveals that ESG ratings improve corporate performance by alleviating financing constraints and enhancing corporate reputation. Furthermore, the performance-enhancing effects of ESG ratings are more pronounced in firms with robust internal controls and private enterprises. This research provides empirical evidence to support stronger ESG investment and the refinement of the ESG rating system.